Enhancement of discharge properties of atmospheric pressure plasma systems through trace radio-frequency oscillation control. (8th July 2021) - Sun, Y; Zhang, Z; Lim, J W M
Abstract: In this work, we report a novel approach that enhances the plasma properties of non-equilibrium plasma under atmospheric pressure using dual-frequency excitation sources. Specifically, these effects are induced by a low frequency of 50 kHz and a higher radio frequency source of 2 MHz. The results show that the application of a small radio-frequency (RF) component in addition to a low-frequency (LF) source improved electron acceleration and thus allows for the excitation to be modulated—through enhancement and suppression of electron impact during each RF period. Electron densities are also enhanced due to the modulated electron impact excitation rate, without an observable increase in gas temperature. When the applied RF component is comparable in magnitude with the low frequency component, the discharge is dominated by influences from the RF component, where the RF electric field provides and improves stability and uniformity simultaneously. This allows for higher input power to be provided to the system.